The Creation of the First (Divinatory) Dream and Enki(g) as the God of Ritual Wisdom - Zgoll, Annette (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
A close reading of the Sumerian version of the Flood Myth shows the god Enki(g) as the creator of the first divinatory dream. Enki(g)’s wisdom is precisely to be understood in this particular way, as ritual wisdom. In addition, Enki(g)’s/Ea’s trick in order to disclose the secrets of the gods without breaking his oath becomes comprehensible: it uses a clever combination of two different types of oracular devices.